FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Gracika Janice Valencia; Anggeraini Oktarida; Choiruddin Choiruddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study investigates the influence of audit opinion, audit findings, audit delay, and independence ratio on the level of financial statement disclosure among regency/city governments in South Sumatra Province. Transparency in public financial management is essential for ensuring government accountability, where financial reports serve as a primary tool for fiscal communication to the public. The research addresses the issue of variation in LKPD disclosure levels across regions, suspected to be influenced by audit quality, timeliness, and fiscal capacity. The objective is to test both the partial and simultaneous effects of these four variables on disclosure level. A quantitative approach is employed using a descriptive method and panel data regression analysis processed with EViews. The sample includes 17 local governments over the 2021–2023 period, yielding 51 observations. The results reveal that, partially, audit opinion and audit delay have significant effects on financial disclosure levels, while audit findings and independence ratio do not. Simultaneously, all four variables show a significant influence. The findings conclude that improving audit opinion quality and reporting timeliness is essential to promote fiscal transparency. Local governments are expected to enhance internal control and reporting efficiency to optimize their financial disclosure levels.